Phosphorene Oxide Quantum Dots Decorated ZnO Nanostructure-Based Hydrogen Gas Sensor - Bhati, Vijendra Singh; Kumar, Ashok; Valappil, Manila Ozhukil; Alwarappan, Subbiah; Kumar, Mahesh (IEEE sensors journal, 2021)
Pristine ZnO based hydrogen sensors pose low sensitivity (~ 43%) at the operating temperature of 150°. Herein, we explore the decoration of Phosphorene oxide quantum dots (POQDs) on RF sputtered grown ZnO nanostructures for hydrogen gas sensing application. A simplistic approach such as drop cast method is employed to decorate electrosynthesized POQDs (2- 8~μ \text{L} ) onto interdigitated electrodes over ZnO nanostructures. The suggested hydrogen sensor based on POQDs ( 6~μ \text{L} )/ZnO nanostructures exhibits an outstanding sensing response (~70.6%) as compared to all the sensors for 100 ppm at 150°C. Enhanced sensing response from the POQDs( 6~μ \text{L} )/ZnO nanostructure might be due to the enormous active surface area of POQDs (provides more active sites for hydrogen gas) and modulation of depletion region at the interface of POQDs and ZnO. The proposed sensor can be operated at mild temperature and consume low power which is the need of the hour for the hydrogen sensors for industrial applications.